Peningkatan Pemahaman Bilangan Asli 1-10 Melalui Model Pembelajaran Guided Discovery Learning pada Peserta Didik Gangguan Spektrum Autisme (GSA) - Lestari, Rizki; Nurhastuti, Nurhastuti; Iswari, Mega; Arnez, Gaby; Yuliana, Syari (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The background of this research stems from the low ability to recognize numbers in children with ASD due to the lack of variety in teaching methods and engaging learning media. This study aims to describe the process and demonstrate the results of applying the Guided Discovery Learning (GDL) model in improving the understanding of natural numbers 1–10 in students with Autism Spectrum Disorder (ASD) at SLB Negeri Muara Bungo. This research uses Classroom Action Research (CAR) conducted in two cycles, each consisting of four meetings. The research subject is a teacher who teaches in a second-grade class. The data were collected through observation and learning outcome tests, and then analyzed qualitatively and quantitatively in a descriptive manner. The research results show a significant increase in the ability to recognize natural numbers 1–10, with the average score of students rising from 15% in the pre-cycle to 65% in Cycle I, and reaching 92% in Cycle II. This improvement demonstrates that the Guided Discovery Learning model is effective in helping GSA children understand number concepts concretely and enjoyably through exploratory activities and gradual guidance.